Nueva gripe A. Cómo enfrentó la crisis el Hospital Italiano de Buenos Aires - Matejic, Patricia; Maluenda, María; Vázquez, Rodrigo; Gil , Néstor; Tejerizo, Juan Carlos (Revista del Hospital Italiano de Buenos Aires, 2009)
.